Praktikeres risikovurderinger: brugen af risikofaktorer i forebyggelsen af ungdomskriminalitet - Ejrnæs, Morten; Monrad, Merete (Nordisk Tidsskrift for Kriminalvidenskab, 2020)
Abstract Social work practitioners support vulnerable children and youth who have problems or are at risk of developing problems. Increasingly, politicians and authorities are emphasizing the role of early crime prevention in social work and the role of risk factors in crime prevention. However, there has not been a focus on how practitioners actually estimate the risk of a young person being apprehended as a first-time offender. We study practitioners’ risk assessments through three vignettes. The vignettes have been constructed using register- and survey-based research on the association between youth crime and a diversity of risk factors. The vignettes are thereby constructed to allow a comparison between the risk assessments of practitioners and the actual risk as demonstrated by the data. The study utilizes a sample of 312 health visitors, teachers (including nursery school teachers) and social workers. The results indicate that practitioners grossly overestimate the risk of apprehension for first-time offences in all three vignettes. The average assessment of the risk is approximately 50 percentage points higher than the actual calculated risk. Furthermore, there is a large variation in the risk assessments given by different practitioners. Moreover, practitioners associate terms such as “high risk” with very different probabilities of crime.